Public-Private Partnership as Tool for Developing Regional Labor Potential - Кruhlov, V.V.; Tereshchenko, D.A. (Наука та інновації, 2019)
Introduction. The modern direction of infrastructure development is the attraction of the private owner by the state under
public-private partnership (PPP) agreements.
Problem Statement. Analysis of the possibilities of PPP for the development of labor potential in the modern labor market,
taking into account the peculiarities of interaction between public and private capital and on the basis of their economic
and social objectives, is an important issue of our time.
Purpose. Justification of the objectives and directions of public-private partnership as a tool for the development of
labor potential, taking into account the main objectives of the implementation of infrastructure projects.
Materials and Methods. Method of theoretical generalization and systematization (to determine the specific features
of forming PPP and labor potential in the modern labor market); monographs (a review of scientific ideas about the problem
of developing PPP, and the sphere of education); statistical method (to present the key figures that characterize PPP and
labor potential); the analytical method (to identify factors that influence implementation of PPP projects as a tool for labor
potential development).
Results. The implementation of PPP projects has been found to stimulate the labor market and to enhance labor capacity.
In case of successful implementation of PPP projects, social problems will be solved due to improved quality of services
in the field of education, healthcare, culture, etc. Implementation of the innovation projects of public-private partnership
in education and science shapes actually the prerequisites for an increase in figures that characterize labor potential
as a whole, and involves staff in specific projects where the key approach is satisfaction of the need for highly qualified
specialists.
Conclusions. The state policies of PPP development, innovational development of the economy and strengthening labor
potential should be aimed at establishing a legislative basis for the institutional environment; introduction of effective
economic mechanisms; establishing up-to-date standards which apply to the key development paths of knowledge-based economy. Вступ. Сучасним напрямом реалізації розбудови інфраструктури є залучення державою приватного власника
в межах договорів про державно-приватне партнерство (ДПП).
Проблематика. Аналіз можливостей ДПП для розвитку трудового потенціалу на сучасному ринку праці, враховуючи особливості взаємодії державного та приватного капіталу та виходячи з їх економічних і соціальних цілей,
є важливим питанням сьогодення.
Мета. Обґрунтування завдань та напрямів державно-приватного партнерства як інструменту розвитку трудового потенціалу, враховуючи основні цілі реалізації інфраструктурних проектів.
Матеріали й методи. Методи теоретичного узагальнення й систематизації (для визначення особливостей формування ДПП і трудового потенціалу на сучасному ринку праці), монографічний (огляд наукових поглядів на проблеми розвитку ДПП), статистичний метод (для відображення показників, що характеризують ДПП і трудовий
потенціал), аналітичний метод (для визначення факторів, що впливають на реалізацію проектів ДПП як інструменту розвитку трудового потенціалу).
Результати. Встановлено, що реалізація проектів ДПП стимулює розвиток ринку праці та підвищує трудовий
потенціал. У разі успішної реалізації проектів ДПП вирішуються соціальні проблеми за рахунок зростання якості
послуг у галузі освіти, медицини, культури та ін. Реалізація інноваційних проектів державно-приватного партнерства
у галузі освіти та науки безпосередньо формує передумови для зростання показників, що визначають трудовий
потенціал в цілому та безпосередньо залучає персонал у конкретні проекти, де ключовим підходом є необхідність у
висококваліфікованих фахівцях.
Висновки. Державна політика розвитку ДПП, інноваційного розвитку економіки та підвищення трудового
по тенціалу повинна спрямовуватися на законодавче формування інституційного середовища, впровадження ефективних економічних механізмів, формування сучасних стандартів, які відповідають основним напрямам розвитку економіки знань. Введение. Современным направлением реализации инфраструктурного развития является привлечение государством частного собственника в рамках договоров о государственно-частном партнерстве (ГЧП).
Проблематика. Анализ возможностей ГЧП для развития трудового потенциала на современном рынке труда,
учитывая особенности взаимодействия государственного и частного капитала и исходя из их экономических и социальных целей, является важным вопросом современности.
Цель. Обоснование задач и направлений государственно-частного партнерства как инструмента развития трудового потенциала, учитывая основные цели реализации инфраструктурных проектов.
Материалы и методы. Методы теоретического обобщения и систематизации (для определения особенностей
формирования ГЧП и трудового потенциала на современном рынке труда); монографический (обзор научных
взглядов на проблемы развития ГЧП); статистический метод (для отображения показателей, характеризующих
ГЧП и трудовой потенциал); аналитический метод (для определения факторов, влияющих на реализацию проектов
ГЧП как инструмента развития трудового потенциала).
Результаты. Установлено, что реализация проектов ГЧП стимулирует развитие рынка труда и повышает трудовой потенциал. В случае успешной реализации проектов ГЧП решаются социальные проблемы за счет роста качества услуг в сфере образования, медицины, культуры и др. Реализация инновационных проектов государственно-частного партнерства в сфере образования и науки непосредственно формирует предпосылки для роста показателей,
определяющих трудовой потенциал в целом и непосредственно привлекает персонал в конкретные проекты, где
ключевым подходом является необходимость в высококвалифицированных специалистах.
Выводы. Государственная политика развития ГЧП, инновационного развития экономики и повышения трудового потенциала должна направляться на законодательное формирование институциональной среды, внедрение эффективных экономических механизмов, формирование современных стандартов, соответствующих основным направлениям развития экономики знаний.